Quality and Safety Considerations for Therapeutic Products Based on Extracellular Vesicles - Yoshinobu Takakura; Rikinari Hanayama; Kazunari Akiyoshi; Shiroh Futaki; Kyoko Hida; Takanori Ichiki; Akiko Ishii‐Watabe; Masahiko Kuroda; Kazushige Maki; Yasuo Miura; Yoshiaki Okada; Naohiro Seo; et al. (2024)
Extracellular vesicles (EVs) serve as an intrinsic system for delivering functional molecules within our body, playing significant roles in diverse physiological phenomena and diseases. Both native and engineered EVs are currently the subject of extensive research as promising therapeutics and drug delivery systems, primarily due to their remarkable attributes, such as targeting capabilities, biocompatibility, and low immunogenicity and mutagenicity. Nevertheless, their clinical application is still a long way off owing to multiple limitations. In this context, the Science Board of the Pharmaceuticals and Medical Devices Agency (PMDA) of Japan has conducted a comprehensive assessment to identify the current issues related to the quality and safety of EV-based therapeutic products. Furthermore, we have presented several examples of the state-of-the-art methodologies employed in EV manufacturing, along with guidelines for critical processes, such as production, purification, characterization, quality evaluation and control, safety assessment, and clinical development and evaluation of EV-based therapeutics. These endeavors aim to facilitate the clinical application of EVs and pave the way for their transformative impact in healthcare.